2010
DOI: 10.1021/jp911069t
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Aldehydes on a Graphite Substrate: Combined Thermodynamic Study of C6−C13 Homologues with a Structural and Dynamical Study of Dodecanal

Abstract: In this work we present a study on the adsorption of linear alkyl aldehydes physisorbed from their bulk liquid onto a graphite substrate combining calorimetry for all homologues from C6 to C13, with more detailed diffraction, incoherent neutron scattering, and scanning tunneling microscopy techniques for one (C12) representative member. We identify solid monolayer formation for some of these species for alkyl chain lengths of 6 to 13 carbons at high surface coverages. The C12 monolayer structure is determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…However, the Moiré pattern or in general, any contrast variation that arises due to specific registry effects on the HOPG surface, is periodic and thus can be easily identified. In fact, due to its periodic appearance, the Moiré pattern has been used to calculate intermolecular distances with accuracy 15c. In the case of Pb‐Pyc , however, the appearance of bright and dark molecules is not periodic, thus ruling out this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Moiré pattern or in general, any contrast variation that arises due to specific registry effects on the HOPG surface, is periodic and thus can be easily identified. In fact, due to its periodic appearance, the Moiré pattern has been used to calculate intermolecular distances with accuracy 15c. In the case of Pb‐Pyc , however, the appearance of bright and dark molecules is not periodic, thus ruling out this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that a difference in registry with an underlying surface can lead to changes in contrast of molecules imaged by STM (and is generally accepted as the cause of the often observed moiré patterns in a molecular layer on top of graphite). 36,41,42 In fact, some research groups use the difference in contrast as a way to quantify the mismatch of adsorbed molecules with the registry of the underlying graphite. 43 We therefore propose that this is the explanation for the observed contrast differences for AuC12 and AuC18.…”
Section: Contrast Differences In Stm Topographymentioning
confidence: 99%
“…It is worth noting that the delicate balance between the hydrogen bond and van der Waals interactions plays an important role in controlling self-assembly polymorphism. Dickerson et al studied polymorphic phenomena by regulating the chain length of isophthalic acid; namely, the self-assembly structure is controlled by the ratio of the two interactions . Although the chain length effects on melting point have been investigated in end-substituted n -alkane homologous series by single-crystal XRD, studies by combining the 2D self-assembly with crystal structure to analyze the relationship between the chain length of alkoxy-substituted conjugated compounds and melting points are relatively scarce. Hence, it is vital to rethink the chain length effects on improving the properties of functional molecules.…”
Section: Introductionmentioning
confidence: 99%